The secret of the old mill - Dixon, Franklin W. (New York Grosset & Dunlap, 2004)
Teenage detectives Frank and Joe Hardy investigate a case of counterfeiting.
At head of title: The Hardy boys.
Series from jacket.
Keywords: Mystery and detective stories; Counterfeits and counterfeiting -- Fiction